Design and Testing of a Simulator for Micro-Vibration Testing of Star Sensor - He Zhu; Shuai He; Xiaoming Wang; Chao Qin; Lin Li; Xiangyang Sun (Micromachines, 2023)
(1) Background: To simulate the micro-vibration environment of the star sensor mounting surface, a multi-dimensional micro-vibration simulator based on the Gough–Stewart platform was designed, which could effectively reproduce space six-dimensional acceleration; (2) Methods: Firstly, the integrated design of a gravity unloading system and micro-vibration simulation platform was adopted, and the first six natural frequencies and mode diagrams of the simulator were obtained by modal analysis. Then, the complete dynamic equation of the simulator was established, and the relationship between the acceleration of the upper platform and the driving force of the legs was deduced, which was verified by co-simulation. Finally, the whole machine test was carried out using the frequency response function based on the actual simulator without multiple iterations; (3) Results: The test results show that the micro-vibration simulator can reproduce space six-dimensional acceleration, with an output bandwidth of 5–300 Hz, and maximum error of 9.19%; (4) Conclusions: The micro-vibration simulator platform has the characteristics of a highly precise, large analog bandwidth and takes up less space, is conducive to transportation, and can accurately reproduce the six-degree-of-freedom space micro-vibrations for the star sensor.